Robust predictive control for two axes synchronous control system - Chen, Baoping. (2008)
The synchronous control with two motion axes is a challenging problem in recent mo-tion control field. The synchronization performance may be degraded by many factors, such as mismatched drive dynamics, disturbances in the system, system parameters variation and system non-linearities. Automatic on-line adjustment of the motion is of importance for imperfect synchronization and output response.